Comparison of Phenotypic and Functional Characteristics Between Canine Non-B, Non-T Natural Killer Lymphocytes and CD3+CD5dimCD21− Cytotoxic Large Granular Lymphocytes - Lee, Soo-Hyeon; Shin, Dong-Jun; Kim, Yoseop; Kim, Cheol-Jung; Lee, Je-Jung; Yoon, Mee Sun; Uong, Tung Nguyen Thanh; Yu, Dohyeon; Jung, Ji-Youn; Cho, Duck; Jung, Bock-Gie; Kim, Sang-Ki; et al. (Frontiers in Immunology, 2018)
Abstract Natural killer (NK) cells play a pivotal role in the immune response against infections and malignant transformation, and adopted transfer of NK cells is thought to be a promising therapeutic approach for cancer patients. Previous reports describing the phenotypic features of canine NK cells have produced inconsistent results. Canine NK cells are still defined as non-B and non-T (CD3–CD21–) large granular lymphocytes. However, a few reports have demonstrated that canine NK cells share the phenotypic characteristics of T lymphocytes, and that CD3+CD5dimCD21– lymphocytes are putative canine NK cells. Based on our previous reports, we hypothesized that phenotypic modulation could occur between these two populations during activation. In this study, we investigated the phenotypic and functional differences between CD3+CD5dimCD21– (cytotoxic large granular lymphocytes, CLGLs) and CD3–CD5–CD21– NK lymphocytes before and after culture of peripheral blood mononuclear cells isolated from normal dogs. The results of this study show that CD3+CD5dimCD21– lymphocytes can be differentiated into non-B, non-T NK (CD3–CD5–CD21–TCRαβ–TCRγδ–GranzymeB+) lymphocytes through phenotypic modulation in response to cytokine stimulation. In vitro studies of purified CD3+CD5dimCD21– cells showed that CD3–CD5–CD21– cells are derived from CD3+CD5dimCD21– cells through phenotypic modulation. CD3+CD5dimCD21– cells share more NK cell functional characteristics compared with CD3–CD5–CD21– cells, including the expression of T-box transcription factors (Eomes, T-bet), the production of granzyme B and interferon-γ, and the expression of NK cell-related molecular receptors such as NKG2D and NKp30. In conclusion, the results of this study suggest that CD3+CD5dimCD21– and CD3–CD5–CD21– cells both contain a subset of putative NK cells, and the difference between the two populations may be due to the degree of maturation.